MEMAHAMI KEMUKJIZATAN AL-QUR’AN : (TINJAUAN ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI) - Muhammad Dirman Rasyid; Anugrah Reskiani (STAIN Majene, 2022)
This study aims to describe the miracles of the Qur'an in terms of ontology, epistemology and axiology. This research is a library research, by collecting related literature from both classical and contemporary sources then presented in a qualitative descriptive manner, then analyzed (content analysis) to arrive at a conclusion. Miracles of the Qur'an is a term that emerged as a response to the inability of humans to match the beauty of language and the message it contains. The Sunni scholars believe that the miracle of the Qur'an comes from itself, while the muktazilah scholars argue that the inability of humans to compete with the Qur'an is due to the existence of al-sarfah (transfer/revocation) ability by Allah swt. to match the Qur'an. As for the degree of miraculousness of the Qur'an, the most common opinion states that it relates to a complete chapter in the Qur'an although it is short. Miracles of the Qur'an include several aspects, namely; al-i‘ja>z al-baya>ni>, al-i‘ja>z al-‘ilmi>, al-i‘ja>z al-Tasyri>‘i>, dan al-i‘ja>z al-gaibi.The miraculous function of the Qur'an is as tangible evidence of the authenticity of the Qur'an which is the word of Allah swt. which occurs in every place and time.